Determinación de las competencias organizacionales en la Avícola C y V de la ciudad de Jipijapa - Ganchozo García, Alan Josué (2021)
Organizational competence is an element of relevance, which refers to the capacities that must exist in each member of an organization, for that reason said research work has as its objective; Determine the organizational competencies of the C and V poultry for the contribution of competitive advantage; and as specific objectives; Characterize the poultry farm C and V of Jipijapa city. Select the organizational skills of the poultry and propose an action plan for the contribution of competitive advantage. The present investigation was carried out in the C and V poultry farm located in Jipijapa city, and for its development, the following types of research were used: bibliographic and field. The methods for its development were: inductive, deductive, descriptive, Delphi with the Kendall indicator and the synthetic analytic. The techniques: interviews, survey, characterization sheet, Ishikawa diagram and 5w + 1h were applied to the process to obtain the result of the investigation. On the other hand, the tools were necessary to obtain the data presented in the study topic, were the interview guide and the questionnaire. It should be noted that the participation of the experts is essential for the corresponding evaluation of the poultry farm members, because in this way it was possible to measure the competencies within the company and their level of performance in terms of their competitive advantage by proposing the plan of improvement for the corresponding corrections.